Acetylcholinesterase Involvement in Apoptosis - Zhang, Xue-Jun; Greenberg, David S. (Frontiers in Molecular Neuroscience, 2012)
To date, more than 40 different types of cells from primary cultures or cell lines have shown AChE expression during apoptosis and after the induction apoptosis by different stimuli. It has been well-established that increased AChE expression or activity is detected in apoptotic cells after apoptotic stimuli in vitro and in vivo, and AChE could be therefore used as a marker of apoptosis. AChE is not an apoptosis initiator, but the cells in which AChE is overexpressed undergo apoptosis more easily than controls. Interestingly, cells with downregulated levels of AChE are not sensitive to apoptosis induction and AChE deficiency can protect against apoptosis. Some tumor cells do not express AChE, but when AChE is introduced into a tumor cell, the cells cease to proliferate and undergo apoptosis more readily. Therefore, AChE can be classified as a tumor suppressor gene. AChE plays a pivotal role in apoptosome formation, and silencing of the AChE gene prevents caspase-9 activation, with consequent decreased cell viability, nuclear condensation and poly (adenosine diphosphate-ribose) polymerase cleavage. AChE is translocated into the nucleus, which may be an important event during apoptosis. Several questions still need to be addressed, and further studies that address the non-classical function of AChE in apoptosis are needed.